Applying multilevel selection to understand cancer evolution and progression. - Lucie Laplane; Anaïs Lamoureux; Harley I Richker; Gissel Marquez Alcaraz; Angelo Fortunato; Zachary Shaffer; Athena Aktipis; Paul S Mischel; Anya Plutynski; Jeffrey P Townsend; Carlo C Maley (PLoS Biology)
Natural selection occurs at multiple levels of organization in cancer. At an organismal level, natural selection has led to the evolution of diverse tumor suppression mechanisms, while at a cellular level, it favors traits that promote cellular proliferation, survival and cancer. Natural selection also occurs at a subcellular level, among collections of cells and even among collections of organisms; selection at these levels could influence the evolution of cancer and cancer suppression mechanisms, affecting cancer risk and treatment strategies. There may also be cancer-like processes happening at different levels of organization, in which uncontrolled proliferation at lower levels may disrupt a higher level of organization. This Essay examines how selection operates across levels, highlighting how we might leverage this understanding to improve cancer research, prevention and treatment.